Severe asthma exists despite suppressed tissue inflammation: findings of the U-BIOPRED study. Issue 5 (6th October 2016) - Wilson, Susan J.; Ward, Jonathan A.; Sousa, Ana R.; Corfield, Julie; Bansal, Aruna T.; De Meulder, Bertrand; Lefaudeux, Diane; Auffray, Charles; Loza, Matthew J.; Baribaud, Frederic; Fitch, Neil; Sterk, Peter J.; et al.
The U-BIOPRED study is a multicentre European study aimed at a better understanding of severe asthma. It included three steroid-treated adult asthma groups (severe nonsmokers (SAn group), severe current/ex-smokers (SAs/ex group) and those with mild–moderate disease (MMA group)) and healthy controls (HC group). The aim of this cross-sectional, bronchoscopy substudy was to compare bronchial immunopathology between these groups. In 158 participants, bronchial biopsies and bronchial epithelial brushings were collected for immunopathologic and transcriptomic analysis. Immunohistochemical analysis of glycol methacrylate resin-embedded biopsies showed there were more mast cells in submucosa of the HC group (33.6 mm −2 ) compared with both severe asthma groups (SAn: 17.4 mm −2, p<0.001; SAs/ex: 22.2 mm −2, p=0.01) and with the MMA group (21.2 mm −2, p=0.01). The number of CD4 + lymphocytes was decreased in the SAs/ex group (4.7 mm −2 ) compared with the SAn (11.6 mm −2, p=0.002), MMA (10.1 mm −2, p=0.008) and HC (10.6 mm −2, p<0.001) groups. No other differences were observed. Affymetrix microarray analysis identified seven probe sets in the bronchial brushing samples that had a positive relationship with submucosal eosinophils. These mapped to COX-2 (cyclo-oxygenase-2), ADAM-7 (disintegrin and metalloproteinase domain-containing protein 7), SLCO1A2 (solute carrier organic anion transporter family member 1A2), TMEFF2 (transmembrane protein with epidermal growth factor like and two follistatin like domains 2) and TRPM-1 (transient receptor potential cation channel subfamily M member 1); the remaining two are unnamed. We conclude that in nonsmoking and smoking patients on currently recommended therapy, severe asthma exists despite suppressed tissue inflammation within the proximal airway wall. Severe asthma exists despite suppressed tissue inflammation in proximal airways when on current recommended therapy http://ow.ly/1rb6303haKP